The dark mirror : the fifth book in the Bone Season series - Shannon, Samantha, 1991- (Shannon, Samantha, 1991- Bone season novel., 2025)
"Paige Mahoney is outside the Republic of Scion for the first time in more than a decade--but she has no idea how she got to the free world. Half a year has been wiped from her memory. Her journey back to the revolution soon takes her to Venice, where the Domino Programme has uncovered evidence of a secret Scion plan. Before Paige can return to London, she must help the network unravel the sinister Operation Ventriloquist, which threatens to bring Europe to its knees in weeks."-- Provided by publisher.